Objek dan Ruang Lingkup Kajian Hadis Masa Klasik dan Kontemporer - Muhammad Anshori (Al Irfani: Journal of Al Qur'anic and Tafsir, 2021)
This paper seeks to map and format new typologies in the study of hadith, ranging from the classical period to the present. As the second source or teaching of Islam after the Qur'an, hadith has an important position in the lives of Muslims. From time to time, traditions continue to be studied with a variety of methods and approaches. The hadith which was originally shaped "the sunnah of the Prophet (living traditions)" began to be studied massively at the beginning of the second century of hijriah, and reached its peak in the 3rd century hijriah. This happened after there was official instruction from the eighth Caliph of the Umayyad Dynasty, namely ‘Umar bin‘ Abdul ‘Azīz (d. 101 H), to several state officials and local hadith scholars. In addition to carrying out the codification (tadwīn) of hadith, previous scholars also wrote literature related to the traditions of hadith. There are two forms or models of the study of hadith science, namely the science of hadith riwāyah and hadith science dirāyah. As time goes by, dirāyah hadith or what is commonly called the science of muṣṭalaḥ al-ḥadīṡ, receives enormous attention from the scholars of hadith. From these two branches of the science of hadith, scholars develop their studies more broadly. The object of the study of hadith which initially consisted of sanad and matan, is now beginning to be studied in a more interesting form after the emergence of thinkers from the Western world or among orientalists. Even including Muslim scholars who are critical of the study of hadith. There are at least four objects and the scope of the hadith study that needs to be studied further, namely the Sanad/Figure Study, Text/Matan Study, Hadith Book Study, and Regional Study. Of the four things, it certainly can be expanded into several separate and detailed studies.